Morbidity and extent of surgical resection of carcinoid tumors after endobronchial treatment. Issue 12 (December 2021) - Reuling, E.M.B.P.; Naves, D.D.; Hartemink, K.J.; van der Heijden, E.H.F.M.; Plaisier, P.W.; Verhagen, A.F.T.M.; Daniels, J.M.A.; Dickhoff, C.
Abstract: Objectives: This study assessed whether endobronchial therapy (EBT) for bronchial carcinoid, if not curative, reduces the extent of the surgical resection and whether EBT is associated with increased surgical morbidity. Material and methods: Analysis was performed in a cohort of patients with bronchial carcinoid who have undergone surgical resection. A group that underwent EBT before the surgery (S + EBT) was compared with a group where no EBT was performed (S-EBT). Postoperative complications were also compared between both groups. Results: A total of 254 patients treated for a bronchial carcinoid tumor between 2003 and 2019 were screened for inclusion. A total of 65 surgically treated patients were included, of whom 41 (63%) underwent EBT prior to surgery. In 5 out of 41 patients (12%) from the S + EBT group, less parenchyma was resected versus 2 out of 24 (8%) from the S-EBT group (OR 1.528, 95% CI 0.273–8.562, p = 1.000). Two patients from the S + EBT group (5%) underwent lobectomy instead of sleeve lobectomy versus 0 from the S-EBT group (OR 1.051, 95% CI 0.981–1.127, p = 0.527). Comparing complications between the S + EBT and S-EBT group did not result in increased postoperative surgical morbidity (15% S + EBT, 24% S-EBT). Conclusion: EBT, if not curative, does not reduce the extent of the subsequent surgical resection. Therefore, if curative EBT is not anticipated, patients should directly be referred for surgery. If curative EBT seems feasible, it should be attempted not only because surgical resection can be prevented, but also because failure of EBT is not associated with excess surgical morbidity.